Needs and Opportunities in Ambient Assisted Living in Portugal - Vardasca, Ricardo (2013)
The exponential raise in the age dependency rate together with the difficulties in having conventional care solutions opens the space for the appearance and development of innovative Ambient Assisted Living (AAL) solutions.However, the development of these solutions requires a thorough understanding of user needs and wills. In this paper we present the scenarios being adopted in the context of AAL projects, as well as the products and services current available in each of the considered utilization scenarios. The needs of the Portuguese AAL users are analyzed through the discussion of some preliminary results from a survey targeted at the Portuguese population over 55 years old. These results will be used to characterize the needs and establish the readiness and willingness of elder Portuguese population in using AAL solutions.